The Influence of Flexible Working Arrangement on Job Satisfaction and Its Impact on Productive Behavior in Employees in Indonesian E-commerce Companies - Maryam Siti Azizah; Imas Soemaryani; Dina Sartika (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
The problem studied in this research is the productive behavior of E-Commerce employees in DKI Jakarta who are currently working with a flexible work system arrangement which turns out to be experiencing a number of challenges. Based on pre-research results, it is known that the productive behavior of E-Commerce employees in Indonesia is relatively low. The visible impact of unproductive work behavior is that it causes individual stress levels to increase, leading to burnout . This research aims to find out the influence of Flexible Working Arrangement on job satisfaction and its impact on productive behavior among E-Commerce employees in Jakarta. The sampling technique is convenience and snowball sampling technique with sample calculation results of 368 respondents. Then verification analysis and factor analysis were carried out using SEM ( Structural Equation Modeling ) using Amos version 24.0.0 software which aims to obtain an appropriate structural model. The research results show that Flexible Working Arrangement has a positive and significant influence on job satisfaction, job satisfaction has a positive and significant influence on productive behavior, and job satisfaction is proven to partially mediate (partial mediation) the influence of Flexible Working Arrangement on productive behavior.